2006
DOI: 10.1007/s10164-006-0012-1
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on over-marking: is it good to be on top?

Abstract: What we refer to as over-marking occurs when one individual places its scent mark on top of, touching, or adjacent to the scent mark of another individual, usually a conspecific. Over-marking frequently occurs among mammals that share common paths, trails, and runways. Despite its ubiquity among terrestrial mammals, we know little about how individuals respond to over-marks and the function(s) of over-marking. Studies on voles and golden hamsters indicate that after exploring an over-mark, individuals respond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 71 publications
(129 reference statements)
0
63
0
Order By: Relevance
“…Our data suggest that overmarking in saddleback tamarins might be the chemical equivalent of physical mate guarding of females as seen in antelopes [Roberts and Dunbar, 2000] and other mammals [for a review, see Ferkin and Pierce, 2007]. During mate guarding, the consort overmarked the female more often than expected, and more than the other male.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our data suggest that overmarking in saddleback tamarins might be the chemical equivalent of physical mate guarding of females as seen in antelopes [Roberts and Dunbar, 2000] and other mammals [for a review, see Ferkin and Pierce, 2007]. During mate guarding, the consort overmarked the female more often than expected, and more than the other male.…”
Section: Discussionmentioning
confidence: 98%
“…This could take the form of (a) overmarking of female scent marks if these contain relevant information on female fertility, in order to conceal it, and (b) allomarking the fertile female. In mammals, marking over a previously deposited scent may fulfil a mate guarding function, either by masking the information from female scents [Roberts and Dunbar, 2000;Ferkin and Pierce, 2007] or by providing information about the male's competitive ability [Rich and Hurst, 1999], or both.…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggest that a female meadow vole's preference for the topscent male donor over the bottom-scent male donor of the over-mark is likely due to the temporal association between the two male scent donors. The top-scent male may represent the most recent individual that has visited the female's territory (Ferkin et al 1999;Woodward et al 2000;Ferkin and Pierce 2007). Specifically, the female's preference may be for the male that was the last to visit and scent marked in her territory, and not the protein content of his diet.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, scent marks are frequently used by these animals to attract opposite-sex conspecifics (Thiessen and Rice 1976;Brown and Macdonald 1985;Ferkin and Seamon 1987). However, many terrestrial mammals, including meadow voles (Microtus pennsylvanicus), place their scent mark on top of the scent mark of a same-sex conspecific, creating an over-mark (Hurst 1990;Johnston 2003;Ferkin et al 2004a, b;Ferkin and Pierce 2007). Recent work has shown that individuals may respond differently to the same two scent donors if they encounter their scent marks first as separate and single scent marks or if they encounter them first as part of an over-mark .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation